2015
DOI: 10.4028/www.scientific.net/amm.773-774.1073
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Utilizing Solid Waste Generated in UNIMAS West Campus

Abstract: The purpose of this study is to identify the solid waste generation and compositions that are generated from UNIMAS West Campus area and also to calculate potential energy and profit that can be harvested from the solid waste. This study was conducted at UNIMAS west campus where the samples of solid waste were collected from different types of source of generation namely residential colleges, faculties, Centre Teaching Facilities (CTF) and cafeteria. The solid wastes collected are weighed, mixed, quartered and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Babich & Smith (2010), Rizk & Perão (2015, Jagau & Vyrastekova (2017), Lorenz et al (2017), Marais et al (2017) and Lorenz & Langen (2018) considered the implementation of information campaigns as a sustainable way to inform students about the negative impact of food waste. Zawawi et al (2015) suggested the implementation of campaigns that emphasize the importance of reducing, recycling and reusing. Kuo & Shih (2016) commented on the importance of efforts by university restaurants to advise consumers to take only what they can eat.…”
Section: Intervention Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Babich & Smith (2010), Rizk & Perão (2015, Jagau & Vyrastekova (2017), Lorenz et al (2017), Marais et al (2017) and Lorenz & Langen (2018) considered the implementation of information campaigns as a sustainable way to inform students about the negative impact of food waste. Zawawi et al (2015) suggested the implementation of campaigns that emphasize the importance of reducing, recycling and reusing. Kuo & Shih (2016) commented on the importance of efforts by university restaurants to advise consumers to take only what they can eat.…”
Section: Intervention Discussionmentioning
confidence: 99%
“…Carneiro (2014) and Zotesso et al (2016) recommended the implementation of an integrated solid waste management system. Babich & Smith (2010) and Zawawi et al (2015) identified the amount of food waste generated, and then calculated the potential energy and profits that could be obtained from the reuse of this waste. Betz et al (2015) recommended re-use and recycling, and concluded that energy production through waste and disposal of food in the trash should be the last resort.…”
Section: Intervention Discussionmentioning
confidence: 99%
“…The implementation of information campaigns is believed to be a sustainable way of informing consumers about the negative impacts of food waste (Jagau & Vyrastekova, 2017;Lorenz & Langen, 2018;Lorenz et al, 2017;Marais et al, 2017;Rizk & Perão, 2015). Zawawi, Rosli, Bustami, Mispan and Ramli (2015) have suggested starting campaigns that emphasize the importance of reducing, recycling and reusing. Dining halls can use campaigns to advise consumers to take only what they really want to eat.…”
Section: Potential Interventions For Food Waste Reductionmentioning
confidence: 99%
“…Given the importance of the benefits that consumers derive from the dining experience, some stress could be caused as a consequence of the introduction of a penalty system, which might compromise any benefits derived. To conclude, food waste management interventions can be used and involve techniques, such as composting (Babich & Smith, 2010;Zawawi et al, 2015), thus enabling economic and environmental impacts to be minimized.…”
Section: Potential Interventions For Food Waste Reductionmentioning
confidence: 99%
“…In recent years, the studies on success factors have been frequently conducted in contexts of product service system [11], wastewater management [12], green building [13], [14], [15], and energy management [16], [17]. Critical success factors (CSF) refer to the limited number of areas in which satisfactory results will ensure successful competitive performance for the individual, department, or organization [18].…”
Section: Critical Success Factors (Csfs) Of Sco Initiativesmentioning
confidence: 99%